2010
DOI: 10.1371/journal.ppat.1000988
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Diversity among Mycobacterium tuberculosis Complex Clinical Isolates: Delineation of Conserved Core and Lineage-Specific Transcriptomes during Intracellular Survival

Abstract: Tuberculosis exerts a tremendous burden on global health, with ∼9 million new infections and ∼2 million deaths annually. The Mycobacterium tuberculosis complex (MTC) was initially regarded as a highly homogeneous population; however, recent data suggest the causative agents of tuberculosis are more genetically and functionally diverse than appreciated previously. The impact of this natural variation on the virulence and clinical manifestations of the pathogen remains largely unknown. This report examines the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
237
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(257 citation statements)
references
References 87 publications
20
237
0
Order By: Relevance
“…Taken together, these results show that CpnT is required for survival and replication of M. tuberculosis in macrophages. Transcriptional profiling showed that cpnT expression is induced under hypoxic conditions (37) and during growth in macrophages (38), but is repressed during nonreplicating persistence (39) and in the presence of reactive oxygen and nitrogen species (40), consistent with the dual role of CpnT in survival of M. tuberculosis in macrophages and in regulating the outer membrane permeability of M. tuberculosis.…”
Section: Duf4237 Family Members (Simentioning
confidence: 66%
“…Taken together, these results show that CpnT is required for survival and replication of M. tuberculosis in macrophages. Transcriptional profiling showed that cpnT expression is induced under hypoxic conditions (37) and during growth in macrophages (38), but is repressed during nonreplicating persistence (39) and in the presence of reactive oxygen and nitrogen species (40), consistent with the dual role of CpnT in survival of M. tuberculosis in macrophages and in regulating the outer membrane permeability of M. tuberculosis.…”
Section: Duf4237 Family Members (Simentioning
confidence: 66%
“…Studies in which nitrate was furnished in vitro revealed that Mtb's ability to respire nitrate allows it to better withstand acid, nitrosative stress (27), or sudden anaerobiosis (28). The evolutionary success of "modern" Mtb strains, which are more prevalent than "ancestral" strains, has been attributed to their enhanced nitrate reductase activity (29,30). Although nitrate and nitrite reproduce the bioactivity of nitric oxide in vivo in a wide array of physiologic processes (16,31,32), reduction of nitrate to nitrite is rarely considered in studies of the host-pathogen relationship in TB.…”
mentioning
confidence: 99%
“…Enhanced expression of these genes was repeatedly observed in the course of mycobacterial infection of macrophages (Fontan et al, 2008;Rohde et al, 2007;Schnappinger et al, 2003;Tailleux et al, 2008). Moreover, dosRS regulon genes were expressed practically in all other conditions: in M. tuberculosis from artificial mouse granulomas, samples of mouse lung tissues and surgical samples of human lung, as well as in samples of sputum and in some experiments in vitro (Garton et al, 2008;Homolka et al, 2010;Karakousis et al, 2004;Li et al, 2010;Talaat et al, 2007;Timm et al, 2003). The functional role of this regulon is still not quite clear, but its activity was suggested to be important for M. tuberculosis adaptation to variations in the redox status during the infection process (Bacon et al, 2004;Bacon & Marsh, 2007;Rustad et al, 2009).…”
Section: Transcription Regulationmentioning
confidence: 94%
“…The papA and pks genes, whose protein products are needed for synthesis of polyketides as components of the M. tuberculosis cell wall (Bhatt et al, 2007;Hatzios et al, 2009;Sirakova et al, 2001), are practically always transcribed in experiments. However, the level of their transcription in vivo varies, possibly reflecting variations in the lipid metabolism depending upon specific conditions Homolka et al, 2010;Rohde et al, 2007;Tailleux et al, 2008). Interestingly, transcription of these genes is decreased in the avirulent M. bovis BCG and M. tuberculosis H37Ra strains as compared with the virulent M. tuberculosis H37Rv strain (Li et al, 2010;Rohde et al, 2007).…”
Section: Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation